Recent advances in the biology and treatment of brain metastases of non-small cell lung cancer: summary of a multidisciplinary roundtable discussion - Preusser, Matthias; Winkler, Frank; Manegold, Christian (ESMO open, 2018)
This article is the result of a round table discussion held at the European Lung Cancer Conference (ELCC) in Geneva in May 2017. Its purpose is to explore and discuss the advances in the knowledge about the biology and treatment of brain metastases originating from non-small cell lung cancer. The authors propose a series of recommendations for research and treatment within the discussed context.
Gesehen am 11.05.2020